Low back biomechanics during manual materials handling of beer kegs - Brents, Colleen, author; Rosecrance, John, advisor; Gilkey, David, committee member; Reiser, Raoul, committee member (Colorado State University. Libraries, 2017)
Biomechanical risk factors such as heavy loads and awkward trunk postures have been associated with occupational low back pain. Those same risk factors are commonly experienced among workers handling beer kegs. The present study used a 3-dimensional motion capture system as a tool to investigate the low back biomechanics during keg handling at a working brewery. Specifically, five workers transferred spent kegs from a pallet to a conveyor to be cleaned and filled with beer in the present study. Data was collected during the portion of the shift workers handled kegs. Low back angular displacements were assessed during keg handling at two heights. Kegs originated from a high or low position and were defined as a high or low lift. Kinematic data from the study was used to estimate compressive and shear forces at the lumbosacral joint from a 2-dimensional static biomechanical model. Repeated measures analyses were performed with each low back angular displacement variable as a function of lift condition. Differences in low back biomechanics between high and low lifts were identified. During low lifts, torso flexion was significantly greater than high lifts. The magnitudes of flexion achieved during low lifts significantly exceeded those of high lifts. Differences between left axial rotation where significant with larger magnitudes of rotation occurring during high lifts. A broader range of angular displacements was observed in high lifts. In both lifting conditions, estimated kinetics exceeded recommended action limits, potentially putting workers at an increased risk for developing low back pain. Work design (lift condition) influenced low back motion during keg handling. Data collection during operational hours was feasible due to the portability and small design of inertial measurement units. Results from the study can help improve workplace design in a craft brewery, reduce risk, and create safer work.